2003
DOI: 10.1182/blood-2002-12-3880
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of the endothelial protein C receptor in human neutrophils

Abstract: Activation of protein C by thrombin bound to thrombomodulin is enhanced by endothelial protein C receptor. This pathway may inhibit inflammation. We investigated effects of protein C and activated protein C on neutrophils as well as whether an endothelial protein C receptor is involved in mediating protein C effects. Neutrophils were from venous blood of healthy donors. Cell migration, respiratory burst, phagocytic activity, and apoptosis were studied by micropore filter assays and fluorometry. Receptor expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 42 publications
10
152
2
4
Order By: Relevance
“…Our results are consistent with subgroup analysis of the PROWESS trial, which revealed that improvement in survival associated with recombinant activated protein C therapy was similar for patients with Gram-positive and Gram-negative bacterial sepsis (46). Our results are also consistent with studies by Sturn et al (34) that examined the effect of activated protein C on neutrophil phagocytosis. The authors reported that activated protein C inhibited neutrophil chemotaxis but did not affect neutrophil respiratory bursts nor phagocytic activity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are consistent with subgroup analysis of the PROWESS trial, which revealed that improvement in survival associated with recombinant activated protein C therapy was similar for patients with Gram-positive and Gram-negative bacterial sepsis (46). Our results are also consistent with studies by Sturn et al (34) that examined the effect of activated protein C on neutrophil phagocytosis. The authors reported that activated protein C inhibited neutrophil chemotaxis but did not affect neutrophil respiratory bursts nor phagocytic activity.…”
Section: Discussionsupporting
confidence: 82%
“…To date, the only known cellular receptor for activated protein C is the EPCR, a 46-kDa singlechain transmembrane glycoprotein homologous to the MHC class I/CD1 family of molecules (33). EPCR was identified originally on vascular endothelial cells and has since been detected in neutrophils (34), monocytes (34), and in the monocytic cell line THP-1 (35). Recent studies in endothelial cells suggest that the antiapoptotic effect of activated protein C is mediated by EPCR and PAR-1 and EPCR (19 -21).…”
Section: Requirement Of Epcr and Par-1 For The Antiapoptotic Effect Omentioning
confidence: 99%
“…For example, THBD and EPCR are both expressed in keratinocytes where their anti-inflammatory roles are particularly relevant to the wound-healing process [35][36][37]. The anti-inflammatory properties of EPCR have also been demonstrated in lung pneumocytes [38], intestinal dendritic cells [39], and in neutrophils [40]. Our findings, as far as we are aware, are the first report of the existence of THBD and EPCR in the anterior pituitary gland.…”
Section: Discussionmentioning
confidence: 51%
“…Natural anti-coagulants do not only oppose the coagulation cascade. Firstly, anti-coagulant processes diminish leukocyte chemotaxis [ 159 ]. They suppress endothelial-cell interactions [ 160 ] as well as apoptosis [ 161 , 162 ].…”
Section: Anti-coagulantsmentioning
confidence: 99%
“…The effect of different concentrations of TF on coagulation kinetics (initiation, propagation and final clot strength) in human plasma is determined [ 159 ]. These analyses demonstrated that an ionised calcium concentration between 1 and 2 mM in the presence of 2000 pM TF was optimal with regard to plateau of time of onset of clotting, velocity of clot formation and maintenance of final clot strength [ 159 ]. Thus, this concentration of TF was utilised in subsequently presented scanning electron microscopy (SEM) data and viscoelastic analysis.…”
Section: Fibrin and Platelet Analysismentioning
confidence: 99%